Inovasi Produk Layanan Administrasi Desa Melalui Aplikasi Banyuwangi Smart Kampung - Daroini, As'ad; Helpiastuti, Selfi Budi; Pamungkas, Tree Setiawan (University of Jember, 2023)
This research aims to analyze product innovation in village administration services through the Banyuwangi Smart Kampung application. This application adds alternative service products at the village level where previously there were other service products, namely village smart websites and self-service platform machines. The presence of the application brings changes to the public service process in Banyuwangi. Previously, services could only be accessed offline or by coming to the village office. Meanwhile, by using the application, the service can be accessed online. In its implementation in the community, there are still several obstacles, starting from the system, which still frequently experiences errors, as well as obstacles from the Banyuwangi community, many of whom don't know about the existence of this application. This research aims to describe the development of Banyuwangi Smart Kampung application service products. This research uses a descriptive qualitative research method using a phenomenological approach. The data analysis technique used is an interactive model data analysis technique. The results of this research show that the Banyuwangi Smart Kampung application can be enjoyed directly by the community because this application makes it very easy for the community to access a service. In implementing the application in society, the government has played an active role in monitoring the implementation of the application by making improvements and updates. The quality of the service product in the form of this application is better than the previous product because, in terms of features and usability, this application is quite complex, namely not only for services at the village level, but can also access services at the district level and can be used for other public services besides administration services. Previously, there was no service product that had the same features and uses as the Banyuwangi Smart Kampung application. Keywords: Product Innovation, Smart Kampung, Application Service Product